Antigone: The conflict between divine law and human law - Tirado Silva, Karim Yardení (2018)
The dilemma that exists between the obedience to divine laws or human laws has existed during all the epochs of humanity. In Antigone, the great work of Sophocles, this dilemma appears clearly. Each of his characters, with different answers and postures, makes it clear that this dilemma may end with choosing obedience to either of the two laws. Antigone decides over any human law, obey the law of the gods, which considers immutable and just for all.